2022
DOI: 10.3390/plants11131733
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Microcystin from Oscillatoria limnetica Lemmermann and Microcystis aeruginosa (Kützing) in Two Leafy Green Vegetable Crop Plants Lactuca sativa L. and Eruca sativa

Abstract: The use of contaminated water to irrigate crop plants poses a risk to human health from the bioaccumulation potential of microcystins (MCs) in the edible tissues of vegetable plants. The main objective of this study is to determine the concentration of total microcystins (MC-LR and MC-RR) in leafy green plants (Lactuca sativa L. var. longifolia and Eruca sativa) that have previously been irrigated with polluted water. Integrated water samples were collected by cleaned plastic bottles at a depth of about 30 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Os resultados indicaram níveis de bioacumulação que excedem até 4 vezes o IDT da OMS, em caso de ingestão dessas hortaliças. Bakr et al (2022) avaliaram cultivos de alface e rúcula irrigados com águas de um lago no Sul do Egito, contendo entre 45-600 μg MCs.L -1 . A pesquisa revelou a bioacumulação de MCs em ambas as hortaliças, alcançando níveis que ultrapassariam o IDT com o consumo de 300 g desses vegetais.…”
Section: Resultsunclassified
“…Os resultados indicaram níveis de bioacumulação que excedem até 4 vezes o IDT da OMS, em caso de ingestão dessas hortaliças. Bakr et al (2022) avaliaram cultivos de alface e rúcula irrigados com águas de um lago no Sul do Egito, contendo entre 45-600 μg MCs.L -1 . A pesquisa revelou a bioacumulação de MCs em ambas as hortaliças, alcançando níveis que ultrapassariam o IDT com o consumo de 300 g desses vegetais.…”
Section: Resultsunclassified
“…Via the aforementioned routes, MC-LR accumulates in the human body. Existing studies have shown that the adult EDI of MCs in plants ranges from 3480–3630 ng/kg/d, both of which are 87–90-fold higher than the WHO detection limit [ 25 ], and the mean concentrations of MCs in the kidney, liver, and muscle of the silver carp were 45.1, 40.0, and 29.1 ng/g, dm, respectively. However, in the presence of dense cyanobacteria blooms, the mean concentrations of MCs in the kidney, liver, and muscle of the silver carp were 782, 957, and 197 ng/g, dm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Microcystins have been shown to cause adverse allelopathic effects on both higher plants [ 33 , 34 , 35 , 36 , 37 ] and phytoplankton [ 9 , 25 , 38 , 39 ]. For example, the three most commonly detected forms of microcystin in water bodies (MC-LR, MC-RR, and MC-YR) cause morphological and physiological changes in Scenedesmus quadricauda , inducing cell aggregation, increasing cell volume, and increasing the production of photosynthetic pigments.…”
Section: Introductionmentioning
confidence: 99%